OPTIMALISASI GIZI SEIMBANG MELALUI EDUKASI "ISI PIRINGKU" PADA MAHASISWA DAN PEKERJA MUDA - Ismi Nur Khasanah; Siti Maryati; Budi Punjastuti; Fahmi Baiquni; Benny Karuniawati (Jurnal Pengabdian Masyarakat Karya Husada (JPMKH), 2025)
Young adults, including students and early-career workers, often maintain unhealthy eating habits due to reliance on fast food and digital delivery services. This community service program aimed to enhance nutritional literacy and healthy diet management skills using the "Isi Piringku" (My Plate) concept. The methods employed included participatory education, food label literacy, and practical simulations for choosing healthy menus at local food stalls (warteg) and through online delivery apps. The program involved 30 participants aged 19-27. Evaluation results showed a significant knowledge increase, with average scores rising from 41.7 to 88.7 (a 47% improvement). Furthermore, 90% of participants successfully demonstrated how to arrange a balanced nutritional plate on a limited budget during simulation sessions. In conclusion, practical simulation-based education effectively changes young adults' perception that healthy eating is affordable and accessible. This initiative is expected to prevent non-communicable diseases by fostering independent and better nutritional choices in the digital era.